Which of the following expressions is the inverse of the function y = 2x − 6? y equals quantity x minus 6 divided by 2 y equals quantity x plus 6 divided by 2 y = 2x + 6 y = �2x + 6

Respuesta :

y equals quantity x plus 6 divided b

Answer:

B. [tex]y=\frac{x+6}{2}[/tex]

Step-by-step explanation:

We have been given an equation [tex]y=2x-6[/tex]. We are asked to find the inverse of our given equation.

To find inverse of our given equation, we will interchange x and y variables and solve for y as shown below:

[tex]x=2y-6[/tex]

Switch sides:

[tex]2y-6=x[/tex]

Add 6 on both sides:

[tex]2y-6+6=x+6[/tex]

[tex]2y=x+6[/tex]

Divide both sides by 2:

[tex]\frac{2y}{2}=\frac{x+6}{2}[/tex]

[tex]y=\frac{x+6}{2}[/tex]

Therefore, the inverse of our given equation would be [tex]y=\frac{x+6}{2}[/tex] and option B is the correct choice.